A new benchmark capacitance for supercapacitor anodes by mixed-valence sulfur-doped V6O(13-x) - Zhai, Teng (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.